2014
DOI: 10.1097/aln.0000435846.28299.e7
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure to Sevoflurane in Mice Causes Deficits in Maternal Behavior Later in Adulthood

Abstract: In an animal model, sevoflurane exposure in the developing brain caused serious impairment of maternal behaviors when fostering their pups, suggesting pervasive impairment of brain functions including innate behavior essential to species survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Sevoflurane is one of the most widely used inhalation anesthetics for pediatric surgery and cesarean delivery due to rapid inhalational induction, tolerable odor, quick emergence and relative cardiovascular stability for infants and children (21). Although sevoflurane exhibits fewer severe effects on the developing brains of animals compared with isoflurane, which is a structurally similar inhaled anesthetic (22), previous studies have demonstrated that sevoflurane may lead to neuronal apoptosis and behavioral dysfunction (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane is one of the most widely used inhalation anesthetics for pediatric surgery and cesarean delivery due to rapid inhalational induction, tolerable odor, quick emergence and relative cardiovascular stability for infants and children (21). Although sevoflurane exhibits fewer severe effects on the developing brains of animals compared with isoflurane, which is a structurally similar inhaled anesthetic (22), previous studies have demonstrated that sevoflurane may lead to neuronal apoptosis and behavioral dysfunction (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…23,27,28,75,76 However, definitive studies that clearly delineate the association between the pediatric use of general anesthetics and sedatives and developmental neurotoxicity are highly desired. in the current study, [ 18 F]-FEPPa was effectively taken up and concentrated into brain ROis in both control and anesthetic-treated monkeys after intravenous injection.…”
Section: Perioperative Medicinementioning
confidence: 99%
“…However, extensive animal model studies have also showed that this anesthetic agent could cause neuronal apoptosis and behavioral dysfunctions [230-232]. …”
Section: Representative Applications Of Shotgun Lipidomics In Biolmentioning
confidence: 99%